Hydrophobic paraffin-selective pillared-layer MOFs for olefin purification. Issue 45 (3rd November 2022) - Jiang, Sisi; Li, Jiaqi; Feng, Meng; Chen, Rundao; Guo, Lidong; Xu, Qianqian; Chen, Lihang; Shen, Fuxing; Zhang, Zhiguo; Yang, Yiwen; Ren, Qilong; Yang, Qiwei; et al.
Abstract : This work reports novel hydrophobic paraffin-selective pillared-layer MOFs realizing efficient adsorption separation of paraffins from olefins. Abstract : Adsorption separation of paraffins and olefins is an industrially important process, while developing a highly stable and paraffin-selective adsorbent remains challenging. Herein, a pcu -topology (primitive cubic) robust pillared MOF, termed M(BTFM)(DABCO)0.5 (H2 BTFM = 2, 5-bis(trifluoromethyl)terephthalic acid, M = Zn, Cu), having a superhydrophobic trifluoromethyl-decorated channel, is able to preferentially adsorb paraffin molecules, affording both high paraffin sorption capacity and selectivity of paraffins over olefins. Benefitting from appropriate pore aperture and functionalized fluoride-rich groups, Zn(BTFM)(DABCO)0.5 possesses a record C3 H8 /C3 H6 uptake ratio (1.11) among propane-selective MOFs reported so far. Remarkably, the purity of olefins including C2 H4 and C3 H6 obtained from breakthrough experiments of paraffin/olefin mixtures (10/90, v/v) reached up to 99.99%. The visualized single-crystal structures of gas-loaded Zn(BTFM)(DABCO)0.5 and DFT calculations both revealed the multiple weak hydrogen-bonding interactions between C2 H6 (or C3 H8 ) and the pore wall, and the stronger binding affinities of a high density of trifluoromethyl groups to C2 –C3 paraffins.